(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
The study aimed to determine the impact of strategic flexibility in achieving competitive advantage in private cement manufacturing companies in the Republic of Yemen. The study used the descriptive analytical approach, and the questionnaire was relied upon as a tool for collecting data. The study population was formed through the method of comprehensive inventory of the occupants of management and specialist positions in the companies under study of (561) individuals, (452) valid questionnaires were retrieved for analysis. The Statistical Package for the Sciences (SPSS) version 20, the statistical program(STATA) (14) and the most important of which is the presence of a high level of practicing strategic flexibility and achieving competitive advantage in private cement manufacturing companies, and the presence of a statistically significant effect of dimensions of strategic flexibility (market flexibility, production flexibility, and human capital flexibility) affect the achievement of competitive advantage in private cement manufacturing companies Among its most important recommendations: adopting strategic flexibility at various levels of decision-making in the companies under study, paying attention to and encouraging new ideas for employees and adopting them, stimulating the creation of a culture of creativity among them.